Knowledge and risk assessment of depression among adolescents during the COVID-19 pandemic - Marianna Charzyńska-Gula; Aneta Sabat; Barbara Ślusarska; Paweł Maciaszczyk; Grażyna Rożek (Kazimierz Wielki University, 2022)
Introduction: Depression, perceived in terms of a health problem, is a disorder that spreads dynamically in the youth population. The COVID-19 pandemic has exacerbated the problem. Aim: The aim of the study was to assess the level of knowledge and the risk of depression in the environment of a selected group of young people in the initial period of the COVID-19 pandemic. Material and methods: The study group consisted of 100 people - school students aged 15-20 years. An original questionnaire and the Kutcher Depression Scale for Youth were used. Results: The level of knowledge of adolescents about the risk factors for depression and symptoms that may indicate depression is average. Young people acquire knowledge from the Internet (41%) and TV programs (16%). Symptoms of depression were more frequent in: older participants of the study, those who assessed their financial situation as low, and students who had experience of depression in their family. The study revealed symptoms of depression in 22% of people. The severity of depression symptoms differed with age, self-esteem and family experience of depression. Conclusions: The obtained results constitute the basis for undertaking urgent preventive measures - both in the educational and psychotherapeutic sphere.